Realizing World-Class Tourism Through the Development of Leading Tourism Areas: An Analysis of Policy Implementation in Kuningan Regency - Wardianto, Diding; Hidayat, Moh. Taufik; Nursahidin (Rescollacom (Research Collaborations Community), 2026)
This study analyzes the implementation of the World Class Tourism Leading Tourism Area (KWU) Development Policy in West Java, with a case study focus on Kuningan Regency. The background of the study is based on the suboptimal implementation of the KWU policy as indicated by infrastructure constraints, limited human resources (HR), weak promotion, cross-stakeholder synergy, and environmental sustainability challenges. This study aims to (1) analyze the implementation of the KWU development policy; (2) identify the forms of innovation implemented; and (3) measure the contribution of KWU to Regional Original Income (also known as PAD in Indonesian) and economic growth in Kuningan Regency. This study uses a descriptive qualitative method, referring to the Van Meter and Van Horn Policy Implementation Model which includes six variables. The results show that the implementation of the KWU policy in Kuningan Regency is not fully optimal. The main obstacles include the uneven distribution of policy standards, limited resources (budget, infrastructure, and HR competencies), and unsynchronized communication and coordination between implementing organizations. Nevertheless, community-based innovation and the integration of cultural/natural/historical attractions, as well as the development of KWU, have been shown to positively contribute to increasing the tourism sector's regional revenue (PAD) and local economic growth. Although this contribution is still dependent on fluctuations in tourist visits and is not yet supported by sustainable tourism product diversification. Overall, it is concluded that strengthening coordination, increasing institutional capacity, and digital innovation are necessary to achieve world-class tourism.